Prevalence of cold dermatoses in kashmir valley: A cross-sectional study from North India - Faizan Y Shah (Indian Dermatology Online Journal, 2020)
Background: Often quoted as ”heaven on earth,” Kashmir forms one of the two divisions of the Union territory of Jammu and Kashmir. A high-altitude region with abundant precipitation and snowfall, the people of Kashmir experience peculiar dermatoses not commonly seen in the majorly tropical subcontinent of India. In this study, we focussed on cold dermatoses as a comprehensive cluster and attempted to study them as a group. Aims: To determine the prevalence of cold dermatoses in Kashmir valley and study their epidemiological characteristics. Methods: This observational, cross-sectional community-based study was conducted on native Kashmiri population in three districts of the valley, exclusively during the winter season of the year 2016–17 and 2017–18. The data were tabulated and analyzed with Chi-square test for discrete variables and t-test for continuous variables, using OpenEpi. A P value of less than 0.05 was taken as significant. Results: The study included a total of 1200 cases with 602 males and 598 females. Perniosis was most commonly encountered dermatoses in our study with a prevalence of 12.2%. Frostbite had a prevalence of 0.83%. Raynaud's phenomenon and asteatotic eczema were seen in 1.5% and 1.67% of the population, respectively. Cold panniculitis, cold urticaria, and livedo reticularis were each seen in 0.08% of the population. Conclusions: Cold dermatoses form an important source of morbidity among the native population of Kashmir. These can be easily prevented by ensuring adequate protection against cold. Creating awareness regarding these disorders and probable association with connective tissue disorders is also imperative.